2010
DOI: 10.31018/jans.v2i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenolic compounds on nematodes- A review

Abstract: Abstract:The term, phenolics has been used to describe a group of structurally diverse plant secondary metabolites. This group includes metabolites derived from the condensation of acetate units (terpenoids), those produced by the modification of aromatic amino acids (phenylpropanoids, cinnamic acid, lignin precursor, catechols and coumarins), flavonoids, isoflavonoids, and tannins. The occurrence and metabolism of phenolic substances in plants, in response to injury or invasion by pathogens, such as fungi, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 20 publications
2
51
0
1
Order By: Relevance
“…Metabolomic analysis of the non-infected and infected treatment showed a separation between the resistant and susceptible plants. This finding indicated that Infected [28]. The amount of caffeid acid was higher in the resistant genotype (GM2) in the infected treatment, but there was no difference in caffeic acid between the genotypes in the control treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Metabolomic analysis of the non-infected and infected treatment showed a separation between the resistant and susceptible plants. This finding indicated that Infected [28]. The amount of caffeid acid was higher in the resistant genotype (GM2) in the infected treatment, but there was no difference in caffeic acid between the genotypes in the control treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Ohri et al (2010) stated that plant secondary metabolites such as phenolic substances produced in response to the invasion of plant pathogens have a defensive role against plant parasitic nematode attacks. In a similar work, Glazer et al (2015) investigated the effect of various plant extracts containing tannin on H. bacteriophora.…”
Section: Discussionmentioning
confidence: 99%
“…The detoxification pathway is conserved across the animal, plant and fungal kingdoms (Blokhina et al , 2003; Xu et al , 2005; Lindholm et al , 2006). In a general manner, the host plant can produce a wide diversity of secondary metabolites with potential effects on PPNs (Ohri and Pannu, 2010; Caretto et al , 2015). The toxic properties of phytoalexins that are secreted in response to nematode infections are specifically seen as xenobiotics (Chitwood, 2002).…”
Section: Section Ii: Potential Key Regulators Of Oxidative Stress Resmentioning
confidence: 99%